Estrogen deficiency in ovariectomized rats: can resistance training re-establish angiogenesis in visceral adipose tissue? (Clinics, 2016)
OBJECTIVE: The purpose of this study was to investigate the effects of resistance training on angiogenesis markers of visceral adipose tissue in ovariectomized rats. METHOD: Adult Sprague-Dawley female rats were divided into four groups (n=6 per group): sham-sedentary, ovariectomized sedentary, sham-resistance training and ovariectomized resistance training. The rats were allowed to climb a 1.1-m vertical ladder with weights attached to their tails and the weights were progressively increased. Sessions were performed three times per week for 10 weeks. Visceral adipose tissue angiogenesis and morphology were analyzed by histology. VEGF-A mRNA and protein levels were analyzed by real-time PCR and ELISA, respectively. RESULTS: Ovariectomy resulted in higher body mass (p=0.0003), adipocyte hypertrophy (p=0.0003), decreased VEGF-A mRNA (p=0.0004) and protein levels (p=0.0009), and decreased micro-vascular density (p=0.0181) in the visceral adipose tissue of the rats. Resistance training for 10 weeks was not able to attenuate the reduced angiogenesis in the visceral adipose tissue of the ovariectomized rats. CONCLUSION: Our findings indicate that the resistance training program used in this study could not ameliorate low angiogenesis in the visceral adipose tissue of ovariectomized rats.